Environmentalists vs oil producers : clearing misunderstandings for constructive action - Archer, L (Oxford Institute for Energy Studies, 1995)
This paper examines the ways in which oil producers and environmentalists interact, their fears and aspirations, the misunderstandings which prevent them from 'hearing' each other's point of view, and the common grounds on which a dialogue leading to constructive action could be achieved.